Vectorial vortex beam detection using plasmonic interferences on a structured gold film. (January 2019) - Wang, Zixiao; Jian, Shuisheng
Highlights: Proposed a structured gold film for vectorial vortices detection. Simultaneously detecting topological charge and spin of vectorial vortices. Capable of detecting both integer and non-integer topological charges. Abstract: Vectorial vortex beams have attracted much attention due to the exotic polarization and phase characteristics. Miniaturized optical elements for vectorial vortices generation and detection are highly desired. In this paper, a vectorial vortex beam detection scheme based on plasmonic interferences on a structured gold film is proposed. The well designed plasmonic structure couples a small portion of energy of the incident beam into surface plasmon polaritons and forms interference patterns. By analyzing interference fringes, spin and orbital angular momentum of incident beams can be detected. The proposed structure has the advantage of realizing nondestructive detection, while the parameters can be adjusted to meet various operation requirements. The proposed scheme provides a new method for on-chip vectorial vortex beam detection.